2020
DOI: 10.1101/2020.04.27.064550
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A conserved neuropeptide system links head and body motor circuits to enable adaptive behavior

Abstract: Neuromodulators promote adaptive behaviors in response to either environmental or internal physiological changes. These responses are often complex and may involve concerted activity changes across circuits that are not physically connected. It is not well understood how neuromodulatory systems act across circuits to elicit complex behavioral responses. Here we show that the C. elegans NLP-12 neuropeptide system shapes responses to food availability by selectively modulating the activity of head and body wall … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 85 publications
(261 reference statements)
1
10
0
Order By: Relevance
“…increased turning frequency for local search, but on prolonged deprivation of food their behavior changes to long runs and dispersal resulting in decreased amplitude [38,69]. We tested a NLP-12(OE) line and found that similar to what was seen previously, the NLP-12(OE) line showed an increase in amplitude of body bends within 30 min off food ( [38,68] Previous studies have shown that NLP-12 peptides function through their receptor CKR-2 in cholinergic motor neurons [37,63,64]. In order to test if CKR-2 is involved in the EIS behavior seen in dop-2 mutants, we tested both ckr-2 and ckr-2; dop-2 double mutants in the EtOH assay.…”
Section: Plos Geneticssupporting
confidence: 59%
See 3 more Smart Citations
“…increased turning frequency for local search, but on prolonged deprivation of food their behavior changes to long runs and dispersal resulting in decreased amplitude [38,69]. We tested a NLP-12(OE) line and found that similar to what was seen previously, the NLP-12(OE) line showed an increase in amplitude of body bends within 30 min off food ( [38,68] Previous studies have shown that NLP-12 peptides function through their receptor CKR-2 in cholinergic motor neurons [37,63,64]. In order to test if CKR-2 is involved in the EIS behavior seen in dop-2 mutants, we tested both ckr-2 and ckr-2; dop-2 double mutants in the EtOH assay.…”
Section: Plos Geneticssupporting
confidence: 59%
“…These data indicate that the increased dopamine seen in dop-2 mutants, signals through DOP-1, increasing NLP-12 release, which in turn functions through CKR-2. Studies have shown that CKR-2 is expressed in motor neurons in the head and along the body of the animal [37,68]. Here we speculate that DOP-2 could be functioning through CKR-2 present on cholinergic motor neurons that are in proximity to the DVA neuron.…”
Section: Plos Geneticsmentioning
confidence: 67%
See 2 more Smart Citations
“…In C. elegans the NPL-12a and 12b peptides only display weak sequence similarities to CCK (see Fig. 1 ), but activate two GPCRs related to CCK receptors (T23B3.4 and Y39A3B.5) [ 25 , 93 ], suggesting the presence of CCK-type signaling in this worm.…”
Section: Cck/sulfakinin Signaling Components In Invertebrates: a Gene...mentioning
confidence: 99%